Distributions of order statistics - Güngör, M.; Bulut, Y.; Çalik, S. (My University, 2009)
In this study, we examined distributions of order statistics corresponding to identically, non-identically, dependent, independent, discrete, continuous and discontinuous random variables and the relations among these distributions.
Keywords: Distribution function; Order statistics; Permanent; Probability density function; Probability function